Japanese fashion designers : the work and influence of Issey Miyake, Yohji Yamamoto and Rei Kawakubo /: the work and influence of Issey Miyake, Yohji Yamamoto and Rei Kawakubo. (2011) - English, Bonnie
No abstract available